Troubleshooting and maintaining Cisco IP networks (TSHOOT) : foundation learning guide : foundation learning for the CCNP TSHOOT 642-832 - Ranjbar, Amir S. (Cisco Press foundation learning series, 2010)
Troubleshooting and Maintaining Cisco IP Networks (TSHOOT) Foundation Learning Guide is a Cisco® authorized learning tool for CCNP preparation. As part of the Cisco Press foundation learning series, this book covers how to maintain and monitor complex enterprise networks. The chapters focus on planning tasks, evaluations of designs, performance measurements, configuring and verifying, and correct troubleshooting procedures and documentation tasks. From this book you will learn the foundational topics for critical analysis, planning, verification and documentation, while configuring tasks would have been mastered in the CCNP ROUTE and CCNP SWITCH material. The author walks you through several real-world troubleshooting examples to help you refine your study in the art of troubleshooting. Each chapter opens with the list of topics covered to clearly identify the focus of that chapter. At the end of each chapter, a summary of key concepts for quick study and review questions provide you with an opportunity to assess and reinforce your understanding of the material. Throughout the book, real-world troubleshooting examples serve to illuminate theoretical concepts. Troubleshooting and Maintaining Cisco IP Networks (TSHOOT) Foundation Learning Guide is ideal for certification candidates who are seeking a tool to learn all the topics covered in the CCNP TSHOOT 642-832 exam. Serves as the official book for the Cisco Networking Academy CCNP TSHOOT course Provides a thorough presentation on maintenance and troubleshooting techniques for routers and switches in a complex enterprise network Covers troubleshooting wireless, unified communications, and video issues in converged networks Explains how to maintain and troubleshoot network security implementations Uses extensive troubleshooting examples and diagrams to solidify the topic explanations Presents self-assessment review questions, chapter objectives, and summaries to facilitate effective studying This volume is in the Certification Self-Study Series offered by Cisco Press®. Books in this series provide officially developed training solutions to help networking professionals understand technology implementations and prepare for the Cisco Career Certifications examinations.